PELATIHAN PENGGUNAAN TEKNOLOGI ARTIFICIAL INTELLIGENCE (AI) DALAM PEMBELAJARAN BAGI PARA GURU SD NEGERI TIAKUR - Patty, Jusak; Lekatompessy, Jeny (Penerbit Widina, Widina Media Utama, 2024)
Primary education is the cornerstone of a nation's development, and in this context, the role of teachers cannot be underestimated. In the rapidly evolving digital era, the integration of technology, particularly artificial intelligence (AI), is key to enhancing the quality of education. This article investigates the implementation of AI training at SD Negeri Tiakur, West Southeast Maluku District, focusing on initial needs analysis, training implementation, and participant response evaluation. The aim is to understand the impact of the training on participants' understanding and acceptance of AI in education. Results show an improvement in participants' understanding of AI concepts and its potential in education, with a positive response to the training material. These findings highlight the importance of practical approaches in introducing new technologies to teachers. As a novelty value, this activity provided an integrated training covering the introduction of basic AI concepts, hands-on practice of AI applications in learning, and the development of AI-based learning strategies independently by the teachers. Recommendations include continuing advanced training to enhance AI usage skills in education and increasing access to technology for teachers. The integration of AI into primary education curricula is expected to prepare students for the challenges of the digital era.ABSTRAKPendidikan dasar adalah pilar utama dalam pembangunan negara, dengan peran penting guru dalam menyampaikan pembelajaran yang efektif. Di era digital, integrasi teknologi, khususnya kecerdasan buatan, menjadi kunci untuk meningkatkan kualitas pembelajaran. Artikel ini mengeksplorasi pelaksanaan pelatihan penggunaan AI di SD Negeri Tiakur, Kabupaten Maluku Barat Daya. Melalui analisis kebutuhan awal, pelaksanaan pelatihan, dan evaluasi respons peserta, kegiatan ini bertujuan untuk memahami dampak pelatihan terhadap pemahaman dan penerimaan terhadap AI dalam pembelajaran. Hasil menunjukkan peningkatan pemahaman peserta tentang konsep AI dan potensinya dalam pendidikan, dengan respons positif terhadap materi pelatihan. Temuan ini menyoroti pentingnya pendekatan praktis dalam mengenalkan teknologi baru kepada guru. Sebagai nilai kebaruan, kegiatan ini menyediakan pelatihan terpadu mulai dari pengenalan konsep dasar AI, praktik aplikasi AI dalam pembelajaran, hingga pengembangan strategi pembelajaran berbasis AI secara mandiri oleh para guru. Rekomendasi termasuk kelanjutan pelatihan lanjutan untuk meningkatkan keterampilan penggunaan AI dalam pembelajaran, serta peningkatan akses terhadap teknologi bagi guru. Integrasi AI dalam kurikulum pendidikan dasar diharapkan dapat mempersiapkan siswa untuk menghadapi tantangan di era digital.